Enhancing Critical Thinking Through General Education: A Study of Student Development - Dimas Setiyawan (JELIM : Journal of Education, Language, Social and Management, 2026)
This study examines the role of general education in enhancing students’ critical thinking skills and supporting their overall intellectual development. In the context of modern education, critical thinking has become an essential competency that enables students to analyze information, evaluate arguments, and make informed decisions. General education, with its interdisciplinary and broad-based approach, provides a strong foundation for fostering these higher-order thinking skills. This research employed a qualitative design to explore students’ and lecturers’ experiences in general education courses. The participants consisted of undergraduate students and lecturers selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and document analysis, including course syllabi and students’ assignments. The data were analyzed using thematic analysis to identify patterns and key themes related to the development of critical thinking skills. The findings reveal that student-centered teaching strategies, such as discussions, debates, and problem-based learning, significantly contribute to the enhancement of critical thinking. Active student engagement and collaborative learning environments were also found to play a crucial role in promoting analytical and reflective thinking. In addition, interdisciplinary learning experiences in general education enable students to connect knowledge across different fields and approach complex problems from multiple perspectives. However, several challenges were identified, including students’ lack of confidence, limited participation, and constraints related to time and class size. In conclusion, general education serves as an effective platform for developing students’ critical thinking skills when supported by appropriate teaching methods, active engagement, and well-designed curricula. The study suggests that educators and institutions should prioritize interactive and student-centered approaches to maximize the potential of general education in fostering critical thinking.